A new species of Dasyhelea Kieffer (Diptera: Ceratopogonidae) from Brazilian Amazonia - Diaz, Florentina; Ronderos, Maria M.; Spinelli, Gustavo R.; Ferreira-Keppler, Ruth L.; Torreias, Sharlane R. S. (Zootaxa, 2013)
A new species from Manaus, Amazonas, Brazil, Dasyhelea eloyi Díaz & Ronderos, is described, illustrated and photomicrograph as larva, pupa and male and female adults based on examination with binocular and scanning electron microscopes. This new species, a typical member of the Dasyhelea grisea species group, is compared with the most similar congeners D. necrophila Spinelli & Rodríguez and the Nearctic D. pseudoincinsurata Waugh & Wirth.